2021
DOI: 10.1523/jneurosci.1244-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Christianson Syndrome Na+/H+Exchanger 6 (NHE6) Causes Abnormal Endosome Maturation and Trafficking Underlying Lysosome Dysfunction in Neurons

Abstract: Award (F31NS093880) and an advanced predoctoral training grant (T32NS062443, PI:Lipscombe/Moore). We thank D. M. Pegtel for kindly providing the CD63-pHluorin construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…Previous studies in NHE6-null mice and rats reported abnormal accumulation of GM2 ganglioside and unesterified cholesterol within late endosomes and lysosomes of neurons and reduced neuronal β-hexosaminidase activity ( Lee et al., 2021 ; Sikora et al., 2016 ; Stromme et al., 2011 ); these phenotypes are typical of lysosomal storage disorders and suggest compromised lysosomal function in NHE6 KO neurons. In addition, we recently found that NHE6-null mouse neurons display defects in endosome maturation and endosome-lysosome fusion, which contribute to deficiencies in lysosome function ( Pescosolido et al., 2021 ). Therefore, here we examined human NHE6 KO neurons for endosomal and lysosomal defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in NHE6-null mice and rats reported abnormal accumulation of GM2 ganglioside and unesterified cholesterol within late endosomes and lysosomes of neurons and reduced neuronal β-hexosaminidase activity ( Lee et al., 2021 ; Sikora et al., 2016 ; Stromme et al., 2011 ); these phenotypes are typical of lysosomal storage disorders and suggest compromised lysosomal function in NHE6 KO neurons. In addition, we recently found that NHE6-null mouse neurons display defects in endosome maturation and endosome-lysosome fusion, which contribute to deficiencies in lysosome function ( Pescosolido et al., 2021 ). Therefore, here we examined human NHE6 KO neurons for endosomal and lysosomal defects.…”
Section: Resultsmentioning
confidence: 99%
“…Neurons from these CS mice exhibit endosomal hyperacidification, a consequence of loss of proton leak from the endosome, as well as impoverished neuronal arborization and attendant circuit dysfunction ( Ouyang et al., 2013 ). NHE6-null mouse neurons also show defects in endosomal maturation and trafficking, which results in enhanced exosome secretion, decreased endosome-lysosome fusion, and lysosome deficiency ( Pescosolido et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the known association of other endosomal NHEs (NHE6 and NHE9) with neurological diseases (e.g. NHE6 for Christianson syndrome and NHE9 for autism and ADHD) ( Kondapalli et al, 2013 ; Ouyang et al, 2013 ; Pescosolido et al, 2014 ; Schwede et al, 2014 ; Prasad et al, 2017 ; Gao et al, 2019 ; Lee et al, 2021 ; Pescosolido et al, 2021 ) and potential functional redundancy of endosomal NHEs, it is possible that NHA2 also has an important, not yet understood, function in the brain or other organs that have not yet been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…NHE6 is mainly expressed in early and recycling endosomes and plays an important role in regulating endosomal pH 49 . Loss of NHE6 function results in overacidification of the endosome 50 , with decreased endosome-lysosome fusion in NHE6-null neurons 51 .…”
Section: Discussionmentioning
confidence: 99%